Can Calvin provide a golden thread in the labyrinth of catechisms available in the church today? - Rensburg, J. Janse van (Koers, 2009)
A congregation can easily get lost in the labyrinth of catechism syllabi available for an educational ministry today. Calvin’s wish was that the church would have one catechism common to all churches. However, he consented to different churches developing different catechisms. He also warned about the power of catechesis, as it has the potential to influence the church for decades to come, and as the body of Christ can be strengthened or wounded through catechesis. Can Calvin provide a golden thread to navigate the labyrinth of catechisms available in the church today? Different models of catechesis are discussed briefly. The similarities and differences with Calvin’s approach to catechism are highlighted, and the article concludes with guidelines for contemporary catechesis.